Friction stir lap welding of dissimilar aluminum alloys with copper particles ?additives - Mohammed Ali, Ghusoon Ridha; Mubarak, Ethar Mohammed; Al-Kalali, Rawaa Hamid; Hussein, Emad Ali (Zielona Góra: Uniwersytet Zielonogórski)
Friction stir lap welding (FSLW) of dissimilar Aluminum alloys (AA1100 with AA6061) is ?investigated using a 3 ?mm sheet`s thick. These alloys are difference in physical characteristics, strength, and melting temperatures, at different tool ?rotation speeds (560, 900 and 1400) rpm and various feed rate (16, 40 and ??125) mm/min, with ?cylindrical pin geometry having two tilt angle: 0°, 3° was used. Copper particles were added ?to ?the weld zone to make composite friction stir welded joints using the best welding ?conditions. Many tests and ?inspections were carried out to evaluate the joint quality and the ?soundness of weldments. The highest value of tensile strength and efficiency at (1400, 40, 3°) while hardness recorded (97.5 HV) at stir zone of FSLW and it go downs along the HAZ and base metals of AA1100 and AA6061.
Keywords: friction stir lap welding (FSLW); micro hardness; copper; AA1100; AA6061